KAJIAN TEORETIS PROSES DIFUSI DI SEKITAR BINTANG NEUTRON - , DONI ANDRA, S.Pd., Dr. rer. nat. Muhammad Farchani Rosyid ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The general relativistic diffusion process on curved space-time manifold around a neutron star has been analyzed. The general relativistic diffusion equation of difusive particles around non-rotating neutron star is derived by constructing phase space in the parametrization of observer time in the hyperbolic coordinate system. This diffusion equation describes the stochastic dynamic of particles around neutron star.